BEBERAPA KAIDAH PENAFSIRAN ALQURAN - Pangeran, Ismail (Hunafa: Jurnal Studia Islamika, 2007)
The Qur’an is the holy book revealed by God to mankind. However, not all verses of the Qur’an are clear in meaning to mankind. Therefore, to understand the contents of the Qur’an, one needs the science of exegesis. In interpreting the verses of the Qura’n, the Quranic interpreters adopt three general approaches such as language approach, ushul approach and logic approach. This article deals with three approaches of interpreting the Qur’an. Kata Kunci: Kaidah penafsiran Alquran, kaidah bahasa, kaidah ushul, kaidah logika